Strengthening Victim Protection and Restorative Justice in Transnational Crime Cases: Legal Harmonization between Civil Remedies and Criminal Prosecution - Linda Ikawati; Yasmirah Mandasari Saragih; Lidya Devega Br. Sinaga (International Forum of Researchers and Lecturers, 2025)
Background: Transnational crime has become increasingly complex and has wide-ranging impacts on victims, while existing legal systems still demonstrate fragmentation between criminal and civil law and remain inadequate in providing effective victim protection and recovery. Research objective: This study aims to analyze and strengthen victim protection in transnational crime through a restorative justice approach, with a particular emphasis on harmonizing criminal and civil legal mechanisms. Method: This study employs a socio-legal approach that integrates normative legal analysis with empirical methods, including case studies, comparative analysis across jurisdictions, and interviews with legal practitioners and non-governmental organizations. Results: The findings indicate that victim protection is hindered by weak restitution enforcement, complex compensation procedures, limited institutional coordination, and cross-border legal barriers. In addition, the implementation of restorative justice in the context of transnational crime remains limited due to the lack of integration within formal legal systems. Therefore, an integrative approach combining criminal law, civil law, and restorative justice is necessary to establish a more comprehensive, effective, and victim-oriented system of protection.